Pulmonary dendritic cell accumulation in usual interstitial pneumonia and nonspecific interstitial pneumonia - Karayama, M.; Inui, N.; Suda, et al., T. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2012)
Background: Pulmonary dendritic cells (DCs) are key regulators of immune responses. An increased accumulation of DCs was reported in the lungs of patients with idiopathic interstitial pneumonia (IIP). Objective: This study aimed to investigate the number of pulmonary DCs in patients with collagen vascular disease associated interstitial lung diseases (CVD-ILDs). Design: Lung tissue samples obtained from 27 patients with IIP and 39 patients with CVD-ILD were detected using monoclonal antibodies against CD1a, CD1c, CD83, Langerin and DC-specific intercellular adhesion molecule-3-grabbing nonintegrin (DC-SIGN). Results: No significant differences in the number or distribution of DCs were observed between patients with IIP and CVD-ILDs.When DC marker expression was analyzed according to pathological subgroup, patients with idiopathic usual interstitial pneumonia (UIP) showed increased DC-SIGN staining when compared with CVDUIP (p